Cationic Net Charge and Counter Ion Type as Antimicrobial Activity Determinant Factors of Short Lipopeptides - Greber, Katarzyna E.; Dawgul, Malgorzata; Kamysz, Wojciech; Sawicki, Wieslaw (Frontiers in Microbiology, 2017)
To get a better insight into the antimicrobial potency of short cationic lipopeptides, 35 new entities were synthesized using solid phase peptide strategy. All newly obtained lipopeptides were designed to be positively charged from +1 to +4. This was achieved by introducing basic amino acid - lysine - into the lipopeptide structure and had a hydrophobic fatty acid chain attached. Lipopeptides were subjected to microbiological tests using reference strains of Gram-negative bacteria: Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonas aeruginosa, Gram-positive bacteria: Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, Enterococcus faecalis, and fungi: Candida albicans, Candida tropicalis, Aspergillus brasiliensis. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimal fungicidal concentration (MFC) were established for each strain. The toxicity toward human cells was determined by hemolysis tests via minimum hemolytic concentration (MHC) determination. The effect of the trifluoroacetic acid (TFA) counter ion on the antimicrobial activity of lipopeptides was also examined by its removing and performing the antimicrobial tests using counter ion-free compounds. The study shows that lipopeptides are more potent against Gram-positive than Gram-negative strains. It was revealed that positive charge equals at least +2 is a necessary condition to observe significant antimicrobial activity, but only when it is balanced with a proper length of hydrophobic fatty acid chain. The hemolytic activity of lipopeptides strongly depends on amino acid composition of the hydrophilic portion of the molecule as well as fatty acid chain length. Compounds endowed with a greater positive charge were more toxic to human erythrocytes. This should be considered during new lipopeptide molecules design. Our studies also revealed the TFA counter ion has no significant effect on the antimicrobial behavior of cationic lipopeptides